2014
DOI: 10.1104/pp.113.230268
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a Calcium-Dependent Protein Kinase Confers Salt and Drought Tolerance in Rice by Preventing Membrane Lipid Peroxidation    

Abstract: The OsCPK4 gene is a member of the complex gene family of calcium-dependent protein kinases in rice (Oryza sativa). Here, we report that OsCPK4 expression is induced by high salinity, drought, and the phytohormone abscisic acid. Moreover, a plasma membrane localization of OsCPK4 was observed by transient expression assays of green fluorescent protein-tagged OsCPK4 in onion (Allium cepa) epidermal cells. Overexpression of OsCPK4 in rice plants significantly enhances tolerance to salt and drought stress. Knockdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
169
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(186 citation statements)
references
References 77 publications
8
169
0
1
Order By: Relevance
“…The MAPKs may further regulate plant cell shapes by interacting with or regulating cortical microtubules, as was shown for MPK4 Beck et al 2011), MPK6 (Müller et al 2010), and MPK12/MPK18 (Walia et al 2009). Recently, Campo et al (2014) reported that overexpression of OsCPK4 enhanced salt tolerance in rice by preventing lipid peroxidation in membranes.…”
Section: Map Kinasesmentioning
confidence: 99%
“…The MAPKs may further regulate plant cell shapes by interacting with or regulating cortical microtubules, as was shown for MPK4 Beck et al 2011), MPK6 (Müller et al 2010), and MPK12/MPK18 (Walia et al 2009). Recently, Campo et al (2014) reported that overexpression of OsCPK4 enhanced salt tolerance in rice by preventing lipid peroxidation in membranes.…”
Section: Map Kinasesmentioning
confidence: 99%
“…Ca 2 þ signals are decoded into phosphorylation signals by the action of several plant-specific proteins such as Ca-dependent protein kinases (CPKs) and Ca/calmodulin-dependent protein kinases (Harper et al, 2004). Transgenic rice plants overexpressing rice CPK4 exhibited enhanced tolerance to salt and drought stress via protecting cellular membranes from stress-induced oxidative damage (Campo et al, 2014). The higher expression level of CPK 1-like (TDF #133-5) in 2.5 μM Bþ1.2 mM Al-treated leaves (Table 1) might provide an adaptive response to Al-toxicity by mitigating Al-induced oxidative-stress.…”
Section: Signal Transduction Genesmentioning
confidence: 99%
“…Thus, tomato LeCDPK2 regulates ethylene biosynthesis in response to wound signalling (Kamiyoshihara et al 2010); Arabidopsis AtCPK1/2/4/5/11 phosphorylate and thereby activate NADPH oxidase to promote reactive oxygen species (ROS) production in response to abiotic and biotic stimuli (Gao et al 2013); rice OsCPK4 participates in rice tolerance to salt and drought stress by protecting cellular membranes from lipid peroxidation (Campo et al 2014), grapevine gene VaCPK29 confers tolerance to heat and osmotic stresses (Dubrovina et al 2017), whereas ZmCPK11 is involved in touch-and wound-induced pathways in maize (Szczegielniak et al 2012). CDPKs are widely involved in various types of disease resistance (Boudsocq et al 2010;Boudsocq and Sheen 2013;Romeis and Herde 2014;Wang et al 2015).…”
Section: Introductionmentioning
confidence: 99%